Peptide Centric Vβ Specific Germline Contacts Shape a Specialist T Cell Response - Wang, Yang; Tsitsiklis, Alexandra; Devoe, Stephanie; Gao, Wei; Chu, H. Hamlet; Zhang, Yan; Li, Wei; Wong, Wing Ki; Deane, Charlotte M.; Neau, David; Slansky, Jill E.; Thomas, Paul G.; et al. (Frontiers in Immunology, 2022)
Certain CD8 T cell responses are particularly effective at controlling infection, as exemplified by elite control of HIV in individuals harboring HLA-B57. To understand the structural features that contribute to CD8 T cell elite control, we focused on a strongly protective CD8 T cell response directed against a parasite-derived peptide (HF10) presented by an atypical MHC-I molecule, H-2Ld. This response exhibits a focused TCR repertoire dominated by Vβ2, and a representative TCR (TG6) in complex with Ld-HF10 reveals an unusual structure in which both MHC and TCR contribute extensively to peptide specificity, along with a parallel footprint of TCR on its pMHC ligand. The parallel footprint is a common feature of Vβ2-containing TCRs and correlates with an unusual Vα-Vβ interface, CDR loop conformations, and Vβ2-specific germline contacts with peptide. Vβ2 and Ld may represent “specialist” components for antigen recognition that allow for particularly strong and focused T cell responses.